1994
DOI: 10.1093/infdis/170.5.1292
|View full text |Cite
|
Sign up to set email alerts
|

Detection Of Drug Resistance Mutations In The Human Immunodeficiency Virus Type I (HIV-I) pol Gene: Differences In Semen And Blood HIV-I RNA And Proviral DNA

Abstract: Different tissues or body fluids in which human immunodeficiency virus type 1 (HIV-1) can reside may contain viruses with distinct characteristics. Sixteen HIV-1-infected patients receiving zidovudine or didanosine were studied cross-sectionally and 1 patient who switched from zidovudine to didanosine was followed sequentially to determine if drug resistance mutations within the HIV-1 pol gene at codons 74 and 215 differed depending on the compartment from which the gene was isolated (plasma, seminal fluid, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 0 publications
0
39
0
3
Order By: Relevance
“…Phylogenetic studies have established that HIV in semen arises from local sources within the male genital tract and/or from passive diffusion via the blood [2][3][4] (previous references in Le Tortorec and Dejucq-Rainsford 5 ). The existence of productive sources in the male genital tract is further substantiated through observations of several differences between blood and semen, including i) detection of persistent infectious HIV in the semen of 5% to 30% of men with undetectable blood viral load receiving fully suppressive antiretroviral therapy [5][6][7][8][9] ; ii) higher viral load in semen in a subpopulation of treatment-naïve men 10 ; iii) different rates, kinetics of emergence, and diversity of drug-resistant strains 4,11,12 ; and iv) different ratio of infected versus noninfected leukocytes. 13 At present, the nature of the sources of HIV in the male genital tract remains unclear.…”
mentioning
confidence: 99%
“…Phylogenetic studies have established that HIV in semen arises from local sources within the male genital tract and/or from passive diffusion via the blood [2][3][4] (previous references in Le Tortorec and Dejucq-Rainsford 5 ). The existence of productive sources in the male genital tract is further substantiated through observations of several differences between blood and semen, including i) detection of persistent infectious HIV in the semen of 5% to 30% of men with undetectable blood viral load receiving fully suppressive antiretroviral therapy [5][6][7][8][9] ; ii) higher viral load in semen in a subpopulation of treatment-naïve men 10 ; iii) different rates, kinetics of emergence, and diversity of drug-resistant strains 4,11,12 ; and iv) different ratio of infected versus noninfected leukocytes. 13 At present, the nature of the sources of HIV in the male genital tract remains unclear.…”
mentioning
confidence: 99%
“…Other studies have shown differential representations of groups of viral sequences from blood, semen (18,114), and genital secretions from women (68,114). Likewise, drug resistance mutations in HIV-1 populations are unequally distributed in the blood and semen (42). Furthermore, marked differences exist among HIV-1 sequences from different tissue compartments, such as the blood, brain, spleen, lymph nodes, and other tissues (5,22,31,35,37,40,52,82,107,108), as well as from subcompartments of a given tissue, such as the white pulp and red pulp of the spleen (30) or the frontal lobe, basal ganglia, medial temporal lobe, and nonmedial temporal lobe of the brain (81).…”
mentioning
confidence: 99%
“…Linkage of the bottleneck protease variant to envelope sequences previously rare in the plasma population could reflect its origin from partially drug-privileged anatomical sites where HIV-1 envelope sequences may differ from those in the plasma (5). The well-documented compartmentalization of distinct env variants in different anatomical sites makes this scenario possible (6,15,17,18,47). The later reemergence of the pretreatment envelope variant while the quasispecies rapidly diversified at the pro locus could reflect selective pressure to restore the initial and presumably optimal env variant in the plasma quasispecies after drug resistance at the pro locus is fully established.…”
mentioning
confidence: 99%